Recurrence and strong stochastic persistence of a stochastic single-species model. (March 2019) - Lv, Jingliang; Zhang, Yan; Zou, Xiaoling
Abstract: A stochastic generalized logistic model is considered in this paper. The condition of the existence of its stationary distribution is generalized. Recurrence and strong stochastic persistence are obtained. Finally some numerical simulations are carried out to support our results.